Managing the risks of outsourcing in supply chain networks - Lee, C. K. M.; Yeung, Y. C.; Hong, Z. (2011 IEEE International Technology Management Conference, 2011)
Outsourcing is comprehensively used by companies to reduce cost so as to response to changing economic pressure. However, as outsourcing has moved from peripheral to more vital functions, it may lead to the risk of loss of control and core competency. In global supply chain, risks constitute single point of failures will lead to disruptions of the supply network. The objective of this paper is to explore both established and emerging risk that may arise from outsourcing and design a simulation model for have quantitative risk of outsourcing activities in the supply chain network. This paper presents a new risk assessment approach to manage and examine the supply chain outsourcing risks. The proposed approach involves a qualitative risk analysis methodology termed as the Supply Chain Risk- Failure Mode and Effect Analysis (SCR-FMEA) which integrates risk identification, analysis and mitigation actions together to evaluate supply chain outsourcing risk. The advantages of using the SCR-FMEA to quantify supply chain outsourcing risk and the major findings of the Monte Carlo Simulation such as how the implementation of delivery outsourcing can reduce both lead time risk and cost risk to the supply chain.